Analisis Fundamental terhadap Kinerja Keuangan PT Bumi Resources Minerals Tbk (BRMS) di Tengah Volatilitas Harga Komoditas Periode 2020-2024 - Syahputra, Rheiga (Maliki Interdisciplinary Journal, 2025)
The volatility of global commodity prices, particularly gold and copper, poses significant challenges to the financial performance of metal mining companies in developing countries. This study aims to analyze the financial performance of PT Bumi Resources Minerals Tbk (BRMS) from 2020 to 2024 using a fundamental analysis approach covering liquidity, solvency, profitability, and valuation ratios. It also examines the impact of commodity price fluctuations on the company’s profitability and proposes risk mitigation strategies based on hedging and capital restructuring. The findings reveal that BRMS’s financial performance is highly sensitive to gold and copper price movements, as reflected in the sharp decline in Return on Equity (ROE) during the 2023 copper price downturn. The company's capital structure, with a debt-to-equity ratio consistently above 150%, exacerbates pressure on net income. Therefore, strategies such as commodity diversification, capital strengthening, and improved transparency are critical to ensure corporate sustainability amidst the depletion of non-renewable natural resources.